Association of interleukin-6 gene polymorphisms and glaucoma: Systematic review and meta-analysis. Issue 4 (July 2021) - Wu, Chien-Liang; Yang, Ya-Ting; Wang, Yuan-Hung; Lin, Tzu-Yu; Lin, I-Chan; Sung, Chih-Wei
Aim: To conduct a systematic review and meta-analysis to explore the association between IL-6 gene polymorphisms ( rs1800795 and rs1524107 ) and glaucoma. Methods: A comprehensive search was performed to select eligible studies regarding IL-6 polymorphisms and glaucoma. The effect sizes in the fixed-effects model were calculated using odds ratios (ORs) with 95% confidence intervals (CIs). Results: Four eligible studies comprising 762 cases and 799 controls were selected for meta-analysis. Regarding the association between the IL-6 rs1800795 polymorphism and glaucoma, those who carried the G/G+G/C genotypes had a non-significant higher risk of glaucoma (OR = 1.29, 95% CI = 0.76–2.19) in the dominant model. However, no obvious association (OR = 0.97, 95% CI = 0.68–1.37) was found for the recessive model (G/G vs G/C+C/C). In the subgroup analysis stratified by ethnicity, no significant associations were observed in populations of Asian or European heritage. Significantly higher glaucoma risks of 15.9 and 99.0 were observed for the dominant (C/C+C/T vs T/T) and recessive (C/C vs C/T+T/T) models, respectively. Conclusion: No statistically significant glaucoma risks were observed for the rs1800795 except rs1524107 polymorphism of IL-6. Further studies with a larger sample size are required to validate the effects of IL-6 polymorphisms on glaucoma risk.